2014
DOI: 10.5194/acp-14-9613-2014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of halogen deposition in polar snow and ice

Abstract: Abstract. The atmospheric chemistry of iodine and bromine in Polar regions is of interest due to the key role of halogens in many atmospheric processes, particularly tropospheric ozone destruction. Bromine is emitted from the open ocean but is enriched above first-year sea ice during springtime bromine explosion events, whereas iodine emission is attributed to biological communities in the open ocean and hosted by sea ice. It has been previously demonstrated that bromine and iodine are present in Antarctic ice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…A similar increase of Br − in snowfall samples after polar sunrise was reported at Alert by Toom-Sauntry & Barrie (2002). Furthermore, Spolaor et al (2013Spolaor et al ( , 2014 found a strong 455 seasonal variability of Br − in polar firn at both Arctic and Antarctic sites, with greater Br − values in spring/summer compared to winter.…”
Section: Atmospheric Deposition On Snow As a Source Of Salinity And Bsupporting
confidence: 77%
“…A similar increase of Br − in snowfall samples after polar sunrise was reported at Alert by Toom-Sauntry & Barrie (2002). Furthermore, Spolaor et al (2013Spolaor et al ( , 2014 found a strong 455 seasonal variability of Br − in polar firn at both Arctic and Antarctic sites, with greater Br − values in spring/summer compared to winter.…”
Section: Atmospheric Deposition On Snow As a Source Of Salinity And Bsupporting
confidence: 77%
“…Satellite measurements have documented a rapid decrease in recent Arctic summer sea ice area (Comiso, 2011;Stroeve et al, 2007). During the last 10 years, the four lowest September sea ice minima of the last 35 years have been recorded (Arctic Sea-Ice Monitor -IJIS, www.ijis.iarc.uaf.…”
Section: Introductionmentioning
confidence: 99%
“…This is compatible with reported seasonality from ice core record (Maselli et al, 2017), with Satellite measurements (Begoin et al, 2010) and modelling studies (Yang et al, 2005), which show a Bromine and Bromine enrichment maximum during the summer months despite the decrease in atmospheric BrO flux observed over summer induced by the reduction of 375 young sea ice and ice salinity due to melting (Maselli et al, 2017). The discrepancy is probably a result of the lag between bromine-containing particles becoming airborne and thus allowing bromine to become enriched above the seawater ratio compared to Na + , and the final deposition (Spolaor et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…It is interesting to notice that the area immediately around Greenland with higher concentration of BrO in the atmospheric column reported by GOME-2 BrO (Spolaor et al, 2014) is indeed the eastern coastal side of Greenland between 75 and 79 ° 420 N, making B17 an ideal site to capture the regional variability of local sea ice extent.…”
Section: Discussionmentioning
confidence: 96%